Pengaruh Budaya Organisasi dan Etos Kerja terhadap Produktivitas Pegawai di Inspektorat Daerah Provinsi Sulawesi Selatan - Asnidar Asnidar; Chalid Imran Musa; Uhud Darmawan Natsir; Muhammad Ilham Wardhana Haeruddin; Rezky Amalia Hamka (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Employee productivity can be influenced by several factors such as organizational culture and work ethic. Based on preliminary observations conducted at the Regional Inspectorate of South Sulawesi Province, there are still issues affecting employee productivity. This study aims to examine and analyze the influence of organizational culture and work ethic on employee productivity at the Regional Inspectorate of South Sulawesi Province. This research uses a quantitative approach with an associative nature. The population in this study consists of all 146 employees of the Regional Inspectorate of South Sulawesi Province, who also serve as the research sample using a census technique. Data collection was conducted through questionnaires, then analyzed using the Structural Equation Model – Partial Least Square (SEM-PLS) method with the Smart-PLS version 4.0 application. The data analysis process included validity testing, reliability testing, and structural model testing. The results of this study indicate that (1) organizational culture partially has no significant effect on employee productivity at the Regional Inspectorate of South Sulawesi Province, (2) work ethic partially has a positive and significant influence on employee productivity at the Regional Inspectorate of South Sulawesi Province, (3) organizational culture and work ethic simultaneously have a significant influence on employee productivity at the Regional Inspectorate of South Sulawesi Province.